Cerebral Phaeohyphomycosis in a Patient with Neurosarcoidosis on Chronic Steroid Therapy Secondary to Recreational Marijuana Usage. (21st February 2013) - Gongidi, Preetam; Sarkar, Debkumar; Behling, Eric; Brody, Joshua
Abstract : Cerebral phaeohyphomycosis is often a fatal disease that typically takes a hematogenous spread after inhalation or accidental skin inoculation of pathogens. We present a patient with a history of heavy marijuana smoking while being on chronic steroid therapy for treatment of neurosarcoidosis who was found to have multiple brain abscesses from Curvularia sp. This is a ubiquitous soil-dwelling dematiaceous fungus that is generally thought to affect solely plants, but there is increasing evidence in the literature of it affecting humans and animals. We review the radiographic findings of neurosarcoidosis and cerebral phaeohyphomycosis as well as the pathophysiology of dematiaceous fungi infections.